2021
DOI: 10.3390/jcm10245976
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Plasma Clots in Adult Patients Following Fontan Procedure: Relation to Clot Permeability and Lysis Time—Multicenter Study

Abstract: Objectives: thromboembolic complications are a major cause of morbidity and mortality following Fontan (FO) surgery. It is also well established that altered FO circulation results in systemic complications, including liver and endothelium damage. We sought to evaluate whether dysfunctions of these sources of hemostatic factors may result in changes of fibrin clot properties. Methods: a permeation coefficient (Ks) and clot lysis time (CLT) were assessed in 66 FO patients, aged 23.0 years [IQR 19.3–27.0], and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Almost all patients after the Fontan procedure develop chronic liver disease, which progress over time [9,10,13]. Hepatic dysfunction in our study was reflected by higher levels of GGT and AST with subsequent deficiency of coagulation factors synthesized in the liver [1,2,9,10,13]. In the current study we showed that hepatic dysfunction contributes to reduced clot contraction and polyhedrocytes formation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Almost all patients after the Fontan procedure develop chronic liver disease, which progress over time [9,10,13]. Hepatic dysfunction in our study was reflected by higher levels of GGT and AST with subsequent deficiency of coagulation factors synthesized in the liver [1,2,9,10,13]. In the current study we showed that hepatic dysfunction contributes to reduced clot contraction and polyhedrocytes formation.…”
Section: Discussionsupporting
confidence: 54%
“…Results of our study may support the concept that liver dysfunction may play a major role in abnormal clot function in Fontan patients. Almost all patients after the Fontan procedure develop chronic liver disease, which progress over time [9,10,13]. Hepatic dysfunction in our study was reflected by higher levels of GGT and AST with subsequent deficiency of coagulation factors synthesized in the liver [1,2,9,10,13].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Patients with Fontan circulation had lower Ks values than controls, and a low Ks value was associated with lower levels of protein C, protein S, and albumin. As in the group of LVAD patients the Ks correlated negatively with brinogen concentration and factor VIII activity 23 .…”
Section: Discussionmentioning
confidence: 68%
“…Well-known risk factors for the development of TEC include chronic venous congestion, high prevalence of supraventricular arrhythmias, the presence of prosthetic material, residual intracardiac shunt, or protein-losing enteropathy [6,7]. We have already shown that adult FO patients are also characterized by hepatic dysfunction as well as enhanced platelet activation, endothelial injury, and impaired fibrinolysis [8,9].…”
Section: Introductionmentioning
confidence: 99%